2008
DOI: 10.1007/s10681-008-9725-2
|View full text |Cite
|
Sign up to set email alerts
|

Pure-lining of flax (Linum usitatissimum L.) genebank accessions for efficiently exploiting and assessing seed character diversity

Abstract: Genetic heterogeneity within genebank accessions of a self-pollinating crop has great implications for their preservation, diversity assessment, utilization and exploitation. This study investigated the intra-accession diversity of 38 flax (Linum usitatissimum L.) genebank accessions preserved by Plant Gene Resources of Canada. Seven quantitative seed characters were studied: 1000 seed weight, seed oil concentration and fatty acid proportion of palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1), lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Long, nonbranched stems, low seed yields, and small seeds are typical traits of fiber flax. However, Diederichsen and Raney reported that there was no association found between seed quantitative (plant height, total seed oil, and α-linolenic acid) and qualitative (stem branching, petal color, and seed color) traits. The absence of correlation between total orbitide content with qualitative and quantitative traits indicates that orbitide expression is independent and should not be affected by changes in these traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long, nonbranched stems, low seed yields, and small seeds are typical traits of fiber flax. However, Diederichsen and Raney reported that there was no association found between seed quantitative (plant height, total seed oil, and α-linolenic acid) and qualitative (stem branching, petal color, and seed color) traits. The absence of correlation between total orbitide content with qualitative and quantitative traits indicates that orbitide expression is independent and should not be affected by changes in these traits.…”
Section: Resultsmentioning
confidence: 99%
“…Diederichsen et al comprehensively details how the core collection was assembled on the basis of characterization and evaluation data . Specifically, six different methods were employed that followed (i) seven qualitative characters (capsule dehiscence, seed color, petal color, anther color, filament color, style color, and ciliation of capsule septa); (ii) quantitative characters (earliness of flowering, plant height, petal width, 1000 seed weight, seed oil content, proportion of the six major fatty acids, seed coat mucilage, and petal measurements); , and (iii) stem fiber content, disease ratings, seed vigor, and drought tolerance. The additional three methods involved inclusion of subsets containing (i) 40 genetically pure lines having extreme low and high values for 1000 seed weight, seed oil content, and fatty acid profiles; (ii) 57 most-distinct accessions based on RAPD markers; and (iii) important fiber-flax cultivars and linseed cultivars from Europe and Canada, respectively . Morphological traits and oil composition of each accession are accessible through the PGRC Web site…”
Section: Introductionmentioning
confidence: 99%
“…Differential performance among flax genotypes under different moisture regimes attributed to variations of their root systems has been reported ( 97 , 177 , 178 ). Linseed is predominantly a rainfed crop in India and therefore Indian genotypes are likely to be more drought tolerant owing to long-time divergent selection under moisture-scarce conditions as also corroborated by several studies ( 97 , 142 , 147 , 179 ).…”
Section: Evaluation Of Linum Germplasm Collectionsmentioning
confidence: 58%
“…Amid the alarming rate of climate change, potential genetic resources from diversity rich and environmentally adapted areas need to be identified for sustainable production. Many studies have reported value-rich and trait-specific promising linseed accession from India, especially high salt and drought tolerant genotypes ( 68 , 142 , 147 , 148 , 179 ). Therefore, the identification of promising donors for economically important traits and novel molecular tags/genes for important traits in the Indian material will add new information to the domain of knowledge, as of now, only PGRC flax core germplasm has been extensively evaluated for various traits.…”
Section: Effective Utilization Of Linum Genetic Re...mentioning
confidence: 99%
“…Selfed F 2 hybrids grown voluntarily with mixed stand from different crosses for F 1 hybrid plants scored the highest variability for almost all characters considered in the study. Diederichsen and Raney (2008) reported there is more genetic variation in this group which influences their phenotype. On seed weight variability, there are different reports: 20.5% as the highest CV from all studied characteristics of 2934 accessions (Diederichsen and Raney, 2006) and 20.8% for 3,089 accessions (Diederichsen, 2007) were for seed weight.…”
Section: Descriptive Statistics and Observational Analysismentioning
confidence: 81%